THE RELATIONSHIP BETWEEN FOOD PARENTING AND SNACKING HABITS WITH THE NUTRITIONAL STATUS OF SCHOOL-AGE CHILDREN - Idcha Kusma Ristanti; Dwi Kurnia P. S.; Nikita Welandha Prasiwi; Aulia Rohmah Purborini (Fakultas Kesehatan, Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2022)
School-age children are the second fastest growing period after toddlers. Where optimal health will produce optimal growth as well. Nutritional intake is needed to meet the physical and mental health of children. This study aims to determine the relationship between maternal eating patterns and children's snack habits with the nutritional status of school-age children. This type of research is correlational analytic with cross sectional time approach. The population is all mothers of school-age children at SDN Ngrandu 1 Kedungadem Bojonegoro in 2022 a total of 88 people, with a sample selected by proportionate stratified random sampling technique obtained 42 respondents. The independent variables in this study were the food parenting in the child and the child's snack habits. The dependent variable is the nutritional status of children. The results obtained after being analyzed using SPSS version 25 with the results of the Spearman test on the relationship between food parenting and the nutritional status of school-age children obtained significant results = 0.000; r = 0.694. The results of the Spearman test on the relationship between children's snack habits and the nutritional status of school-age children obtained significant results = 0.001; r = 0.493. From the description above, it can be concluded that there is a significant relationship between maternal eating patterns and children's snack habits with the nutritional status of school-age children (6-12 years) at SDN Ngrandu 1 Kedungadem. Keywords: School Age Children, Parenting, Snacking Habits, Nutritional Status